Investigation of second language writing anxiety among ESL students in public university / Nur Aziela Aidit, Sheela Faizura Nik Fauzi and Esther John Perry - Aidit, Nur Aziela; Nik Fauzi, Sheela Faizura; John Perry, Esther (UiTM Press, 2023)
In order to achieve quality education in English especially writing skills, comprehension of Second Language Writing Anxiety (SLWA) needs to be investigated. Hence, the study aims to analyse SLWA among ESL students at public universities. The study's specific goals are to answer the following questions: (1) What factors contribute to SLWA?, (2) What impact does SLWA have on students' academic writing abilities? and (3) What are some suggestions to reduce SLWA? 103 Diploma (70 females, 33 males) students from Universiti Teknologi MARA, Samarahan Campus, participated in the study. A questionnaire was shared via Google Forms. The findings depicted a total of 54.3% (n = 56) of the pupils expressed their utmost anxiety about their peers and the teacher's negative evaluations.